Respuesta :

Esther

Answer:

[tex]3x^2 + 14x + 8 = (3x+2)(x+4)[/tex]

[tex]x^2-10x+25=(x-5)^2[/tex]

Step-by-step explanation:

[tex]x^2 - 26 = (x-6)^2[/tex]

[tex](x-6)(x-6)[/tex]

[tex]x^2-6x-6x+36[/tex]

[tex]x^2-12x+36[/tex] (wrong)

[tex]3x^2 + 14x + 8 = (3x+2)(x+4)[/tex]

[tex](3x+2)(x+4)[/tex]

[tex]3x^2+12x+2x+8[/tex]

[tex]3x^2+14x+8[/tex] (true)

[tex]x^2-7x+10=(x+5)(x+2)[/tex]

[tex](x+5)(x+2)[/tex]

[tex]x^2+2x+5x+10[/tex]

[tex]x^2+7x+10[/tex] (wrong)

[tex]x^2-10x+25=(x-5)^2[/tex]

[tex](x-5)^2[/tex]

[tex](x-5)(x-5)[/tex]

[tex]x^2-5x-5x+25[/tex]

[tex]x^2-10x+25[/tex] (true)

Hope this helps!

ACCESS MORE